Extraction, purification, structure, modification, and biological activity of traditional Chinese medicine polysaccharides: A review - Xue, Hongkun; Li, Pengcheng; Bian, Jiayue; Gao, Yuchao; Sang, Yumei; Tan, Jiaqi (Frontiers in Nutrition, 2022)
Traditional Chinese medicines (TCM), as the unique natural resource, are rich in polysaccharides, polyphenols, proteins, amino acid, fats, vitamins, and other components. Hence, TCM have high medical and nutritional values. Polysaccharides are regarded one of the most critical bioactive components in TCM. Growing reports have indicated that TCM polysaccharides (TCMPs) have various biological activities, such as antioxidant, anti-aging, immunomodulatory, hypoglycemic, hypolipidemic, anti-tumor, anti-inflammatory, and other activities. Hence, the research progresses and future prospects of TCMPs must be systematically reviewed to promote their better understanding. The aim of this review is to provide comprehensive and systematic recombinant information on the extraction, purification, structure, chemical modification, biological activities, and potential mechanism of TCMPs to support their therapeutic effects and health functions. The findings provide new valuable insights and theoretical basis for future research and development of TCMPs.